Anthropometry in Children with Transfusion-Dependent Beta-Thalassemia Major - Nisa, Noor Un; Ikram, Farooq; Tahir, Muhammad (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the abnormal anthropometric findings among children diagnosed with and managed for transfusiondependent beta-thalassemia major. Study Design: Cross-sectional study. Place and Duration of Study: Department of Paediatric Medicine, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Sep 2019 to Aug 2020. Methodology: This study involved 310 children of both genders aged 2 to 18 years presenting with beta-thalassemia Major receiving multiple blood transfusions. Anthropometric findings, including height and weight for age, were measured and plotted via World Health Organization-2007 growth charts in all the study participants. Relevant socio-demographic variables, including serum ferritin, were correlated with abnormal anthropometric findings among these children. Results: The mean age of the patients was 8.87±7.42 years. 170(54.8%) male and 140(45.2%) female patients were in the study group. Most of the children [218 (70.3%)] had any abnormal an-thropometric findings, either weight or height for age, while 92 (29.7%) had no anthropometric abnormality. Majority of the patients [198 (63.8%)] patients had stunted growth, while 170 (54.8%) were underweight. Longer duration of transfusion and raised serum ferritin levels had a statistically significant correlation with any anthropometric abnormality among the beta-thalassemia major patients (p-value<0.05). Conclusion: More than 70% of the patients suffering from beta thalassemia major had abnormal anthropometric findings. Height was affected more than weight among these individuals. Patients with longer duration of transfusion dependence and raised serum ferritin levels were more at risk of developing anthropometric abnormality in our target population.